Diagnosis and Treatment of Traumatic Carotid Artery Dissection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Nineteen reports of pediatric cases of extracranial traumatic carotid artery dissection (CAD), obtained through PubMed search, were reviewed by researchers at Texas Children's Hospital and Baylor College of Medicine, Houston, TX.